Improving control quality of PMSM drive systems based on adaptive fuzzy sliding control method - Tran Duc Chuyen; Roan Van Hoa; Hoang Dinh Co; Tran Thi Huong; Pham Thi Thu Ha; Bui Thi Hai Linh; Tung Lam Nguyen (Institute of Advanced Engineering and Science, 2022)
In this paper, a solution to improve the precision in speed control for permanent magnet synchronous motors (PMSM) based on fuzzy adaptive sliding mode controller (FASMC) is proposed. In order to tackle the nonlinear tracking problem, continuously switching topologies are embedded. The designed algorithm and the closed electric drive system stability is examined by employing corresponding Lyapunov candidate functions. The results are numerically simulated and experimentally verified in the environment of MATLAB-Simulink, control Desk with dSPACE 1104 card, proving the applicability of the control algorithm which not only works well in simulations but also in practice for possible industrial traction drive applications.